Pendidikan Internasionalisasi Pondok Pesantren: Studi Kasus di Pondok Pesantren Al-Istiqomah Petanahan, Kebumen - siti Chaizatul Munasiroh (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2018)
Abstract Discussing about the role of Islamic boarding schools in the formation and development of education, especially Islamic education, in Indonesia is hardly debated and doubtful. Long before Indonesia's independence, this institution which was in charge of ulama (kyai) was present in the archipelago. The history that goes through shows that the pesantren is not only able to maintain the survival of the times, but also can take care of its development which continues to increase from time to time. According to available data, this institution was first established, especially in Java, in the 15th century by Maulana Malik Ibrahim (one of the oldest walisongo) and later developed by other walisongo. By the end of the 19th century, the number of Islamic boarding schools in Java had grown to 300, and based on the records of the Indonesian Ministry of Religion Islamic Boarding School Database, the number of Islamic Boarding Schools in 2018 was around 21,321. The survival and continuous development of the boarding school certainly cannot be separated from the scientific tradition developed which has a strong enough distinction. One of them is the transformative education pattern. This makes the pesantren not just a religious institution that is merely active in the world of religious education for the santri, but at the same time has a concern and active role together with the community in empowering themselves. These values ??also did not escape the Al-Istiqomah Islamic Boarding School in Kebumen. This pesantren which is famous for its 'Arab Village' has more value which requires the Al-Istiqomah Islamic boarding school to be developed into an international standard education. This internationalization is important to be put forward, in addition to developing and strengthening the quality of Islamic boarding schools in Indonesia and in Kebumen in particular, Internationalization will also be the biggest contribution to the development and strengthening of its own academic community. It will also make Islamic boarding schools play a greater role in making concrete contributions to global life. Keywords: Survive Management of Islamic Boarding Schools, International Islamic Education, Quality of Islamic Boarding Schools